Memory and brain function - Montemayor, Jose C. Jr. (Manila : Central Books, 2022)
This book therefore sets out the basics of MEMORY AND BRAIN FUNCTIONS, how it can occur and progressively develop to an otherwise healthy individual or even in persons with comorbidities and set forth more aggressive goal to attain the objectives of holistic health. This book covers also the different aspects of treatment protocols and the significance of further prevention by properly applying THE BASICS OF MEMORY AND BRAIN FUNCTION.
Includes bibliographical references.
Keywords: BRAIN